Hydrogen bond based smart polymer for highly selective and tunable capture of multiply phosphorylated peptides - Guangyan Qing (Nature Portfolio, 2017)
Capture of low-abundance multiply phosphorylated peptides (MPPs) is difficult due to limitation of enrichment materials and their interactions with phosphates. Here the authors show, a smart polymer driven by specific but tunable hydrogen bonding interactions can differentially complex with MPPs, singly phosphorylated and non-modified peptides.